Trapped at the bottom of the sea - Peretti, Frank E. (Wheaton, Ill. : Crossway Books, 1990)
Lila leaves her father in Japan to stay with her aunt in Seattle. But the Air Force flight she is on is hijacked, and then presumed to have crashed. The race is on to find her and the secret weapons pod before another hostile group does.
Previously issued in series: A Cooper family adventure.
"Youth fiction/10-14"--P. 4 of cover.
Keywords: Christian life -- Fiction; Adventure and adventurers -- Fiction; Christian life -- Juvenile fiction; Adventure and adventurers -- Juvenile fiction